Son preference and household income in rural China. - Knight, J; Shi, L; Quheng, D (Routledge, 2010)
Why is it that couples who have a son or whose last child is a son earn higher conditional income? To solve this curious case we tell a detective story: evidence of a phenomenon to be explained, a parade of suspects, a process of elimination from the enquiry, and then the denouement. Given the draconian family planning policy and a common perception that there is strong son preference in rural China, we postulate two main hypotheses: income-based sex selection making it more likely that richer households have sons, and an incentive for households with sons to raise their income. Tests of each hypothesis are conducted. Taken as a whole, the tests cannot reject either hypothesis but they tend to favour the incentive hypothesis; and there is evidence in support of the channels through which the incentive effect might operate. To our knowledge, this is the first study to test these hypotheses against each other in rural China and more generally in developing countries.